Risk of transmission of Vibrio parahaemolyticus in foods - New, Chia Yeung; Anyi, Ubong; K., Nur Hasria; A., Nur Fatihah; Radu, Son (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2016)
Vibrio parahaemolyticus is well known to be abundantly distributed in marine, coastal and estuarine environments. Since 1951, V. parahaemolyticus had been the source of numerous outbreaks related to contaminated or mishandled seafood. However, V. parahaemolyticus had been detected on other types of food. This issue has prompted this study to investigate on the prevalence of V. parahaemolyticus in various food samples and determine the risk associated with it. The results of the MPN-plating technique of the study indicated that V. parahaemolyticus was detected in seafood (33.3%, 95% Confidence Interval [CI] 31.9 - 34.8, 94 - 290 MPN/g) and vegetables (10.0%, 95% CI 9.7 - 10.3, 9.2 - 23 MPN/g) while negative V. parahaemolyticus was detected in fruits (0.0%, 95% CI 0 - 1, < 3 MPN/g) and chicken (0.0%, 95% CI 0 - 1.5, < 3 MPN/g). Microbial risk assessment using at risk was conducted based on the data collected on separate food classes. The probability of illness of consuming contaminated seafood and vegetables with V. parahaemolyticus was 1.86 x 10-8 with a rate of 0.505 per 100,000 Malaysians and 4.83 x 10-9 with a rate of 0.002 per 100,000 Malaysians respectively. The risk of consuming both contaminated seafood and vegetables was simulated and the probability of illness was 2.34 x 10-8 with 249 expected cases to occur per year and a rate of 0.831 per 100,000 Malaysians. The underlying factors that contribute to the transmission of V. parahaemolyticus can cause an increased risk of infection and should be prevented to conserve the public health.